CHURCH THE BRIDE AND CHRIST THE BRIDEGROOM - Kalambukattu, Naiju Jose (Asian Horizons, 2016)
The nature and significance of the Church, and her relation with Christ have been expounded through various images and models. The East Syriac Fathers explicate the profound relation and intimate union between the Church and Christ by the image of the bride and bridegroom. As a pledge of His love for the bride and as a foretaste of the heavenly banquet, Christ has hallowed and adorned her with His body and blood as spiritual food and drink. The Church the bride born from the side of Christ the bridegroom has the same mission of Christ in the world. How genuine is she in imbibing and interiorizing the vision and accomplishing and achieving the mission of her Groom — is the query.